A Study of the Instructional Media Used by the English Teachers in Teaching English - Ristika, Ni Putu Rika; Ratminingsih, Ni Made; Pratiwi, N. P. A (LPPM Undiksha, 2020)
This study was a descriptive qualitative which intended to investigate the types of instructional media used and the implementation done by the English teachers. The instructional media used to become the best solution to overcome the learning problems faced by the teachers. The subjects of this study were 5 English teachers at SMPN 2 Melaya. The data were collected through observation during the teaching and learning process and interviews with the teachers. The data analyzed descriptively. From the overall findings, the English teachers used eight types of instructional media, such as; real objects or models, slides, pictures, video, web, audio, books, and the boards. The teachers had different ways to implement them, such as they used LCD Projector and speakers as the tools to show the material and the school environment as the realia. The lack of facilities became the main problem in implementing them. Moreover, the teachers tend to use the same instructional media for the other topic since they do not have enough time to prepare.